Integrated preparation and properties of polyurethane‐based sandwich structure composites with foamed core layer. Issue 9 (15th June 2021) - Zeng, Xiaoyan; Tang, Ting; An, Jiaxuan; Liu, Xiaoxiang; Xiang, Hongxia; Li, Youbing; Yang, Chaolong; Xia, Tian
Abstract: The polyurethane‐based sandwich structure composite was integrally prepared through using glass fiber reinforced polyurethane composite (GFRPUC) as the skin layer and rigid polyurethane foam (RPUF) as the core layer with the application of a prepolymer infiltrating‐foaming integrated manufacturing process. The effect of isocyanate content on the mechanical properties of polyurethane (PU) matrix was explored, and the influences of n‐pentane as the foaming agent on the mechanical properties of RPUF and sandwich structure composite were investigated. The results showed that PU prepolymer synthesized with 10% isocyanate group had the excellent comprehensive performances including the tensile strength of 77 MPa, bending strength of 110 MPa and impact toughness of 59 kJ/m 2 . Under the optimal molding process, the tensile strength, bending, and impact strengths of the GFRPUC surface are 794 MPa, 846 MPa, and 228 kJ/m 2, respectively. Using the PU prepolymer method, the surface layer and foam core are integrally fabricated as the sandwich structure composites, whose structure is characterized by strong surface layer and porous core with energy absorption effect. The integrated SSC plate with foamed core layer has excellent mechanical properties especially the core layer containing 2 wt% foaming agent, such as shear property. Abstract :